PENGARUH KEBIJAKAN SUKU BUNGA LPS, KREDIT YANG DIBERIKAN DAN SIMPANAN DANA MASYARAKAT TERHADAP KENAIKAN ASET BPR (STUDI KASUS DI PT. BPR RESTU KLATEN MAKMUR TAHUN 2006-2013) - Kuswandari, Erna; Setyawanti, Dandang (Kiat Bisnis, 2014)
Research type is quantitative research. Data type which digunakanadalah dokumenter, and data source is data sekunder. Technique of data collecting use the documentation. Technique analyse the data use the doubled linear regresi.  Result of research conclude: (1) There no influence negative mount the policy of rate of interest of LPS to asset amount in Prosperous BPR Restuklaten; (2) There is positive influence of credit given to level of amount of asset of Prosperous BPR Restu Klaten; (3) There no positive influence of deposit of society fund to level of amount of asset of Prosperous BPR Restu Klaten; (4) There is positive influence mount the policy of rate of interest LPS, credit given by dansimpanan of society fund by together to amount of asset of Prosperous BPR Restu Klaten. Keywords :      Policy of Rate Of Interest LPS, Given Credit, Deposit of Fund of Society and Increase of Asset BPR